Utilizing neurodegenerative markers for the diagnostic evaluation of amyotrophic lateral sclerosis - Klíčová, Kateřina; Mareš, Jan; Menšíková, Kateřina; Kaiserová, Michaela; Friedecký, David; Kaňovský, Petr; Strnad, Miroslav; Matěj, Radoslav (European journal of medical research, 2024)
BACKGROUND: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disorder characterized by progressive deterioration of upper and lower motor neurons. A definitive diagnostic test or biomarker for ALS is currently unavailable, leading to a diagnostic delay following the onset of initial symptoms. Our study focused on cerebrospinal fluid (CSF) concentrations of clusterin, tau protein, phosphorylated tau protein, and beta-amyloid1-42 in ALS patients and a control group. METHODS: Our study involved 54 ALS patients and 58 control subjects. Among the ALS patients, 14 presented with bulbar-onset ALS, and 40 with limb-onset ALS. We quantified biomarker levels using enzyme-linked immunosorbent assay (ELISA) and compared the results using the Mann-Whitney U-test. RESULTS: Significant elevations in neurodegenerative markers, including tau protein (p < 0.0001), phosphorylated tau protein (p < 0.0001), and clusterin (p = 0.038), were observed in ALS patients compared to controls. Elevated levels of tau protein and phosphorylated tau protein were also noted in both bulbar and limb-onset ALS patients. However, no significant difference was observed for beta-amyloid1-42. ROC analysis identified tau protein (AUC = 0.767) and p-tau protein (AUC = 0.719) as statistically significant predictors for ALS. CONCLUSION: Our study demonstrates that neurodegenerative marker levels indicate an ongoing neurodegenerative process in ALS. Nonetheless, the progression of ALS cannot be predicted solely based on these markers. The discovery of a specific biomarker could potentially complement existing diagnostic criteria for ALS.
Keywords: Delayed Diagnosis; amyotrofická laterální skleróza; tau Proteins; proteiny tau; klusterin; Amyotrophic Lateral Sclerosis; Humans; Biomarkers; biologické markery; opožděná diagnóza; lidé; Clusterin